Analisis Produksi Padi Sawah di Desa Kalawara Kecamatan Gumbasa Kabupaten Sigi - Reny Reny (Mitra Sains, 2019)
The purpose of this study was to analyze the factors that affect the production of paddy rice farming in the village of Kalawara, the District of Gumbasa. The research was conducted in the village of Kalawara, District of Gumbasa, The Regency of Sigi with the consideration that the village is one of the largest rice using Mekongga rice seed. The population in this study are the farmers of paddy in the village numbering 169 people, by the determination of the sample, the number of respondents who were sampled as much as 20% of the total population of 169 farmers, in order to obtain a total sample of 34 farmers, respectively Mekongga seed as many as 18 farmers and other seed for 16 farmers. Based on the analysis using a model Production function Cobb-Douglas then obtained as follows: land area (X1), seeds (X2), urea (X3), fertilizer Phonska (X4), labor (X5),) and dummy use of seeds together (simultaneously) very significant effect on production or variable (Y), partially each variable (land, seed, fertilizer urea, fertilizer Phonska, labor, pesticides and dummy use of seeds effect on very significant effect on farm production of paddy in the village. The coefficient of determination (R2) of 0.960 indicates that the variation (rise and fall) farm production of paddy (Y) in the village can be explained by the independent variables (Xi) by 96%, while 4% were caused by other factors not included in the model, for example climatic factors and others.